Ambient Air Pollution and its Association with the Respiratory Health of Asthmatic Primary School Children in Selected Urban, Rural and Industrial Areas in Selangor and Kuala Lumpur - Zakaria, Junaidah (2010)
Background: The influence of air pollution on asthma and allergies still remains a debate. Many researches have shown that air pollution could affect the respiratory health especially for susceptible groups such as asthmatic children. A cross-sectional comparative study was intended to analyze the association of air pollution and respiratory health in asthmatic children from January to December 2008. Objective: The main objective of this research was to study the association between air pollution exposures with the respiratory health among asthmatic primary school children living in selected urban, rural and industrial areas in Selangor and Kuala Lumpur. Methodology: A total of 207 respondents involved in this study, 87 were children from urban area, 67 children from industrial area and another 53 from rural area. The selection of respondents was based on purposive sampling method, only asthmatic children who had been diagnosed by a physician were involved. Health records of the children were obtained from the school administration. Respondents were children from Standard 2 to Standard 5, with informed consent from their parents. A modified ISAAC Questionnaire translated into the Malay language was administered and completed by parents. Peak expiratory flow (PEF) readings were measured using a peak flow meter mini weight model AFS CE 0120 on Monday, Wednesday and Friday before and after school. Urine samples were collected to measure the oxidative stress (8-OHdG) levels among respondents. Continuous ambient air pollutants (PM10, CO, SO2, and NO2) data monitored by Alam Sekitar Malaysia were obtained from the Department of Environment. The 8 hours indoor air pollutants (PM10, PM2.5, CO, SO2 and NO2) were measured by using Giliair air sampling pump. The standard NIOSH methods were referred to in the measurement. Results: The prevalence of asthma from students’ health record was higher in urban and industrial children than those of the rural children. In 2008, the annual mean PM10 concentrations were slightly higher than the Malaysian Ambient Air Quality Guideline (MAAQG) in the industrial area (64.922μg/m3) and the PM10 for urban and rural area were 48.687μg/m3 and 23.464μg/m3 respectively. Sulfur dioxide was significantly higher in the industrial area with a mean of 0.003ppm compared to the urban area of 0.002ppm, whereas, higher levels of CO were recorded in urban area (1.305ppm), followed by industrial area (0.873ppm) and rural area (0.680ppm). Similarly, higher levels of NO2 were recorded in urban area (0.029ppm), followed by industrial area (0.021ppm) and rural area (0.010ppm). For household indoor air quality, there were significant differences in the PM10, PM2.5 and CO concentrations whereby PM10 were the highest among industrial houses with a mean of 0.0071μg/m3 followed by the urban with 0.0042μg/m3 and the rural area with 0.0012μg/m3. Indoor carbon monoxide was highest in the urban houses with a mean concentration of 0.204ppm. There was an association between the prevalence of respiratory and allergy symptoms with locations. Urban children have a higher count of symptoms for difficulty in breathing, (χ2=9.34, p<0.001) chest tightness, (χ2=9.66, p<0.05) and wheezing (χ2=12.01, p<0.05). Allergy symptoms were also higher among urban children such as skin rashes, nasal symptoms and itchy with watery eyes and nose. Results showed a significant influence of days within week and PEF reading before and after school. The oxidative stress (8-OHdG) was high among the urban children with a mean (5.072ng/mg creatinine) followed by industrial children (3.587ng/mg creatinine) and rural children (3.090ng/mg creatinine). The severity of asthma among respondents was classified according to PEF variability, day and night symptoms and respiratory scores. Most of the children had mild asthma and moderate asthma. From the logistic regression, fathers’ education, PEF variability and allergy to pollen significantly influenced the frequency of asthmatic attack among respondents. Factors which significantly influenced the asthma severity were PM10 and allergy to pollen. Conclusion: The air pollutants were higher in the urban and industrial area. This study shows that the asthmatic children who live in urban and industrial areas have greater risk of developing severe asthma due to exposure to air pollutants. Keywords: asthma, school children, air pollutants, peak expiratory flow,8-OHdg and severity.